Critical coupling with graphene-based hyperbolic metamaterials - Xiang, Yuanjiang (2014)
In order to effectively realize and control the critical coupling, a graphene-based hyperbolic metamaterial has been proposed to replace the absorbing thin film in the critically coupled resonance structure. Our calculations demonstrate that the critical coupling effect (near-perfect light absorption) can be achieved at the near-infrared wavelength by using this layered structure, while the critical coupling frequency can be tuned by varying the Fermi energy level of graphene sheets via electrostatic biasing. Moreover, we show that the critical coupling frequency can be tuned by changing the thickness of the dielectric or layer number of the graphene sheets in the unit cell of the graphene-dielectric HMM. The optimization performance has also been indicated, which may offer an opportunity towards the experimental designs of high efficient graphene based critical coupling devices.